Reading the times : temporality and history in twentieth-century fiction - Stevenson, Randall (Edinburgh University Press, 2018)
From the Prime Meridian Conference of 1884 to the celebration of the millennium in 2000; from the fiction of Joseph Conrad to the novels of William Gibson and W.G. Sebald, Reading the Times offers fresh insight into modern narrative.